Enhancement Material Removal Rate Optimization of Sinker EDM Process Parameters Using a Rectangular Graphite Electrode - Sumanto Sumanto; Acim Maulana; Dodi Mulyadi; Khoirudin Khoirudin; Siswanto Siswanto; Sukarman Sukarman; Ade Suhara; Safril Safril (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2022)
This article discusses the optimization of sinker electrical discharge machining (sinker EDM) processes using SPHC material that has been hardened. The sinker EDM method is widely employed, for example, in the production of moulds, dies, and automotive and aeronautical components. There is neither contact nor a cutting force between the electrode and the work material in sinker EDM. The disadvantage of the sinker EDM is its low material removal rate. This work aims to optimize the material removal rate (MRR) using graphene electrodes in a rectangular configuration. The SPHC material was selected to determine the optimum MRR model of the sinker EDM input parameter. The Taguchi experimental design was chosen. The Taguchi technique used three input parameters and three experimental levels. Pulse current (I), spark on time (Ton), and gap voltage were among the input parameters (Vg). The graphite rectangle was chosen as an electrode material. The input parameter effect was evaluated by S/N ratio analysis. The result showed that pulse current has the most significant impact on material removal rate in the initial study, followed by spark on time and gap voltage. All input parameters are directly proportional to the MRR. For optimal material removal rate, the third level of pulse current, spark on time, and gap voltage must be maintained. In addition, the proposed Taguchi optimization model could be applied to an existing workshop floor as a simple and practical electronic tool for predicting wear and future research.